Methodological challenges in sport and leisure research with youth from refugee backgrounds. Issue 4 (2nd October 2019) - Francis Cain, Tashana; Trussell, Dawn E.
ABSTRACT: Research has pointed to the capacity of sport and leisure to help newcomer youth adapt to a new country, yet research has not distinguished the unique experiences between immigrant youth and refugee youth. In this article, we focus on the challenges and difficulties of doing research with newcomer youth who have a refugee background, particularly related to ethics and recruitment challenges. Three key sets of issues are discussed: facing language barriers and communication challenges, encountering difficulties with gatekeepers and building relationships in the community, and negotiating refugees' fears and perceptions towards research. We take an interdisciplinary approach and draw insights from diverse fields of study as we consider lessons learned along the way. Although focused on recruitment challenges and the research process, the issues brought to the forefront of this paper also serve to emphasize practical implications and the delivery of programmes in the community.